System Analysis of Globalization Processes’ Axiological Evaluation on the Bolon Process Ethiology and Chronology - Kondur, Oksana; Katsero, Oksana; Trubchanina, Irina (Publishing Office UR, Rzeszów, 2020)
It is justified that the cross-border educational coordination activities have drawn public attention to the global challenges of the 21st century and have declared the necessity for sustainable development education to be at the forefront in the progress concept and strategies towards sustainability. Therefore, it is necessary to create a sustainable development specialists’ professional training system, especially, for the professionals with managerial and qualitative competences.
Keywords: education for sustainable development; vocational training; qualitative competence; quality of education; management in education